Rare Glomerular Presentation of Essential Cryoglobulinemia without HCV Infection - Marković, Dragana; Djurić, Petar; Janković, Aleksandar; Bogdanović, Ljiljana; Pešić, Snežana; Dimković, Nada; Naumović, Radomir (Archives of Clinical and Medical Case Reports, 2021)
Membranoproliferative glomerulonephritis (MPGN) is characterized by mesangial cell proliferation and structural changes in glomerular capillary walls and double-contoured glomerular basement membrane (GBM). Usually, it is connected with cryoglobulinemia which is defined by the presence of a circulating, a cold-precipitating immunoglobulin. The chemical and immunological features of the cryoglobulins are used to define three types of cryoglobulinemia. In this report we describe the third case of MPGN type II with essential cryoglobulinemia without HCV infection, which is usually defined in the literature as MPGN type II. Here, we present 61-years old woman previously diagnosed with MPGN in 2012 at another institution. At that time, she was not examined in terms of cryoglobulinemia. Initially she was treated with pulses of methylprednisolone, then oral corticosteroids until cessation when complete remission was achieved. Meanwhile, she had two relapses of the disease. In October 2020 we re-evaluated her and found out positive cryoglobulins in repeating testing. Serological studies for anti-neutrophil cytoplasmic antibodies (ANCA), myeloperoxidase and proteinase 3, anti-double stranded DNA antibodies, anti-hepatitis C antibodies, anti-HIV antibodies and anti-hepatitis B surface antibodies were all negative. Serum M protein or monoclonal IgM were not detected. Percutaneous renal biopsy was compatible with the diagnosis of MPGN. Based on clinical, laboratory and histological evaluation, it was concluded that the patient had a MPGN with essential cryoglobulinemia. Therapy with mycophenolate mofetil had a beneficial effect on the course of disease and the patient achieved partial remission and stabile renal function for the last 3 months of follow-up. Since the therapy for MPGN with essential cryoglobulinemia is not standardized, further research in the field is needed.